Kontribusi Perempuan Pesisir dalam Ekonomi Pariwisata: Studi Kasus Pantai Tanjung Bira, Kabupaten Bulukumba - A. Octamaya Tenri Awaru; Muhammad Aksa (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The aim of this study is to analyze the contribution of coastal women to the tourism economy in Tanjung Bira Beach, Bulukumba Regency, as well as the challenges they face. The method employed is a qualitative approach, which includes in-depth interviews, participatory observation, and documentation studies involving women from diverse backgrounds engaged in tourism activities. The findings indicate that coastal women play a significant role in creating job opportunities and increasing family income, while also contributing to the preservation of local culture. The discussion highlights the need for interventions to empower women through training programs and improved access to resources, considering the challenges they encounter such as limited capital and policy support. The impact of this study is expected to raise awareness of the importance of women’s roles in the tourism economy and assist policymakers in formulating more inclusive strategies for empowering women in coastal areas